2021
DOI: 10.1097/pec.0000000000002406
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pediatric Maxillofacial Injury

Abstract: Objective: Isolated facial injuries are less common among pediatric trauma patients. The literature has focused on, especially, fractures in facial injuries. There is a limited number of studies evaluating all facial injuries in childhood. The study aims to evaluate the clinical characteristics of maxillofacial injuries and to identify patients who require further intervention. Methods:The data from pediatric patients with maxillofacial injury (<18 years) between January 2011 and December 2015 were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Characteristics of 58 studies 7,9,11,21–75 included in the meta‐analysis are shown in Table 1. The studies included a case range of 37–183,336 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of 58 studies 7,9,11,21–75 included in the meta‐analysis are shown in Table 1. The studies included a case range of 37–183,336 cases.…”
Section: Resultsmentioning
confidence: 99%